Functional analysis of novel allelic variants in URAT1 and GLUT9 causing renal hypouricemia type 1 and 2 - Mancikova, Andrea; Krylov, Vladimir; Hurba, Olha; Sebesta, Ivan; Nakamura, Makiko; Ichida, Kimiyoshi; Stiburkova, Blanka (Clinical and experimental nephrology, 2016)
BACKGROUND: Renal hypouricemia is a rare heterogeneous inherited disorder characterized by impaired tubular uric acid transport with severe complications, such as acute kidney injury and nephrolithiasis. Type 1 is caused by a loss-of-function mutation in the SLC22A12 gene (URAT1), while type 2 is caused by defects in the SLC2A9 gene (GLUT9). METHODS AND RESULTS: In this article we present clinical, biochemical and molecular genetics of two Czech patients. The serum uric acid in the probands was 57 and 98 µmol/l and expressed as an increase in the fractional excretion of uric acid (40 and 18 %). The sequencing analysis of SLC22A12 and SLC2A9 revealed novel variants p.R92C and p.R203C in URAT1 and p.G72D in GLUT9. Functional studies were performed for these novel variants and for previously reported variants p.I118HfsX27, p.G216R and p.N333S in GLUT9 responsible for renal hypouricemia in three probands from Czech Republic and United Kingdom. Functional studies showed significantly decreased urate uptake for all variants. However, urate uptake of GLUT9 variants prepared for both isoforms were not significantly different. CONCLUSIONS: This is the first complex function characterization of non-synonymous allelic variants in patients with renal hypouricemia regarding both GLUT9 isoforms. Our finding of defects in the SLC2A9 and SLC22A12 genes show the following: renal hypouricemia is not restricted to East Asia populations; urate uptake of GLUT9 variants prepared for both isoforms were not significantly different; renal hypouricemia type 2 has more wide clinical variability than type 1; the phenotypic severity of renal hypouricemia is not correlated with results of functional characterizations of URAT1 and GLUT9 variants.
Keywords: Female; lidé středního věku; Animals; Organic Cation Transport Proteins; GLUT9; Adolescent; Urinary Calculi; SLC2A9; Renal hypouricemia; Humans; mutační analýza DNA; vrozené poruchy tubulárního transportu; URAT1; lidé; Middle Aged; Organic Anion Transporters; zvířata; Uric acid transporters; Glucose Transport Proteins, Facilitative; proteiny přenášející organické kationty; Renal Tubular Transport, Inborn Errors; ženské pohlaví; Child; proteiny usnadňující transport glukosy; SLC22A12; přenašeče organických aniontů; dítě; DNA Mutational Analysis; močové kameny; Xenopus; mladiství